MUCINOUS ADENOCARCINOMA OVARY: DIAGNOSTIC DILEMMA AND THE USEFULNESS OF COLONOSCOPY - Mehmood, Shafqat; Khan, Muhammad Qayyum (Journal of Ayub Medical College Abbottabad, 2015)
Background: Ovarian carcinoma is the fourth most common malignant disease of women. Types of ovarian carcinoma, including serous, mucinous, endometrioid, and transitional carcinoma, differ from each other with respect to morphology, genetic alterations and in their clinical course.Ovary is a common site for tumour metastases with 5-30% of ovarian cancers metastatic in nature. Differentiating primary from metastatic mucinous ovarian adenocarcinoma is often challenging. We assessed the usefulness of colonoscopy to sort out this dilemma. Methods: In this case-series with retrospective data collection at a tertiary care hospital in Pakistan, demographics, indication for referral, tumour size, laterality, and the immuno-histochemical stains were recorded. Results: A total of 17 patients were referred to gastroenterology department between March 2009 and March 2012. Mean age of the patients was 36.7 years (range, 16-58 years) and the indication for referral was mucinous pathology. All of these patients had surgery outside hospital; histopathology was submitted at our pathology laboratory for review. Out of 17 patients, 16 had progressive abdominal distension as the primary symptom whereas one patient had a history of bleeding per rectum; 67% (12/17) of the tumours were more than 10cm and 94% (16/ 17) were unilateral. We were able to find the colorectal primary in 17.4% (3/17) of the patients, whereas upper GI endoscopies were unrevealing all patients. CK-7 was positive in two of three and CK-20 was positive in all the three patients with colorectal primary. Conclusion: We were able to identify gastrointestinal primary in significant number of patients without gastrointestinal symptoms that showed immuno-histochemical stain pattern of primary mucinous adenocarcinoma and had a tumour size of greater than 10cm and were unilateral. Keywords: Mucinous adenocarcinoma of the ovary, Colonoscopy, Algorithm